Implementasi Digital Marketing Menggunakan Platform E-Commerce dan Media Sosial Terhadap Masyarakat Dalam Melakukan Pembelian - adhitya, wisnu rayhan; Teviana, Tengku; Sienny, Sienny; Hidayat, Ahmad; Khaira, Imamul (TIN: Terapan Informatika Nusantara, 2024)
This research aims to determine the implementation of digital marketing using e-commerce platforms and social media for the public in making purchases. The aim of implementing digital marketing using e-commerce platforms and social media for people to make purchases includes several important aspects, namely that e-commerce platforms and social media enable businesses to reach a wider audience globally. By leveraging this technology, businesses can get their products or services in front of more people, increasing their chances of attracting new customers. E-commerce makes it easy for people to make purchases anytime and anywhere without having to come to a physical store. A fast and easy purchasing process improves the customer experience and drives loyalty. Through social media and e-commerce platforms, businesses can collect data on consumer preferences and behavior. This data is used to create more relevant and personalized marketing campaigns, thereby increasing the likelihood of conversion. Social media allows businesses to interact directly with customers, receive feedback and build stronger relationships. This interaction can increase customer trust and encourage them to make purchases. Digital marketing is usually more cost efficient compared to traditional marketing. Businesses can reach a large audience with a smaller budget through online advertising and promotions on social media. Digital platforms provide tools to measure and analyze marketing campaign performance in real-time. This data helps businesses to evaluate their strategies and make necessary adjustments to improve results. Digital marketing allows businesses to be more creative in their marketing approach. Interactive content, videos, and other creative campaigns can capture audience attention and make brands stand out. Through social media, businesses can work with influencers to expand their reach and leverage user-generated content to increase brand authenticity and trust. By effectively utilizing e-commerce and social media platforms, businesses can achieve their marketing goals more efficiently, increase sales and build stronger relationships with customers.